THE SCIENTIFIC-EXPERIMENTAL BASES OF IMPROVING OF ORGANIZATION OF EPIDEMIOLOGICAL SURVEILLANCE ON NONPOLIOENTEROVIRUS INFECTIONS IN AZERBAIJAN - Rustamova, L.I. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Solving specific problems posed at each level of EN for improving the epidemiological surveillance of non-polioenterovirus (NPEV) infections. Material and methods: Statistics on the incidence of “intestinal infections of unknown etiology” and “non-polioenterovirus infections” in 2001-2005 were analyzed. Results: In order to improve the epidemiological surveillance of non-polioenterovirus infections, one should take into account such indicators as the monthly and intra-annual incidence of non-polioenterovirus infections, the serotypic spectrum of isolated non-polioenteroviruses from patients and from surface and wastewater, biological features of the identified nonpolioenteroviruses (especially virulence), molecular-genetic monitoring children and adults of non-polioenteroviruses, epidemiological nepolioenterovirusnymi forecasting of disease infection in the subsequent years. Conclusions: The determination of the agent by marker features allows you to obtain important information about the virulent properties of the strain and take adequate anti-epidemic measures.